Parque urbano lineal en la quebrada de los tiestos cabecera municipal de Pitalito-Huila (2022)
The project "linear urban park in the municipal seat of PitalitoHuila, located in commune 3" central "of the municipality of Pitalito, is a proposal for (Improvement and development of natural spaces) and the recovery of the environmental zone an d water body Zanjón de los Tiestos of the central commune, with the purpose of reestablishing all the environmental components The cohesion of the city with the new areas that are being developed on the territory, arises from the need to organize and struc ture the urban landscape system, the research is fixed on the soils of urban expansion, areas that are catalysts of movement, development and not urban flows, in this area the urban edge converges, normally it is a space conceived as a strip, limit or bord er between urban activities and the sector.